Asymptotically Statistical Equivalent of Order ? in Amenable Semigroups - Altin, Yavuz; Et, Mikail; Altinok, Hifsi (E D P Sciences, 2017)
In this study we introduce the concepts of asymptotically statistical equivalent functions of order alpha and strong asymptotically equivalent functions of order alpha defined on discrete countable amenable semigroups.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Convergence; Summability; Sequences; Spaces